Thirty-Year Follow-Up of Early Onset Amyotrophic Lateral Sclerosis with a Pathogenic Variant in SPTLC1 - Aparna Ajjarapu; Shawna ME. Feely; Michael E. Shy; Christina Trout; Stephan Zuchner; Steven A. Moore; Katherine D. Mathews (Case Reports in Neurology, 2023)
Dominant mutations in serine palmitoyltransferase long chain base subunit 1 (SPTLC1), a known cause of hereditary sensory autonomic neuropathy type 1 (HSAN1), are a recently identified cause of juvenile amyotrophic lateral sclerosis (JALS) with slow progression. We present a case of SPTLC1-associated JALS followed for 30 years. She was initially evaluated at age 22 years for upper extremity weakness. She experienced gradual decline in muscle strength with development of weakness and hyperreflexia in lower extremities and diffuse fasciculations in the upper extremities at 26 years. She lost independent ambulation at age 45 years. Pulmonary function declined from a forced vital capacity of 94% predicted at 27 years to 49% predicted at 47 years, and she was hospitalized twice for respiratory failure. To our knowledge, this is the longest documented follow-up period of JALS caused by a de novo pathogenic variant in SPTLC1.